Pituitary volumes in patients with adjustment disorder - Atmaca, Murad; Bibar, Alper; Tabara, Muhammed Fatih; Koc, Mustafa; Gurok, Mehmet Gurkan; Korkmaz, Sevda; Yildirim, Hanefi (Oxford Univ Press Inc, 2024)
The pituitary gland plays an important role in the stress response mechanism. Given the direct link between adjustment disorder and stress, we hypothesized that there might be changes in the pituitary gland in these patients. The study comprised a patient group of 19 individuals with adjustment disorder according to the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition, and 18 healthy controls. The mean pituitary gland volumes of the patient group were not statistically significantly different from those of the healthy control group (80.81 +/- 1.82 mm(3) in patients with adjustment disorder vs. 81.10 +/- 7.04 mm(3) in healthy controls, with a statistically nonsignificant difference of P > 0.05). This finding is contrary to our previous findings in anxiety-related disorders. In this regard, adjustment disorder is not similar to anxiety-related disorders in terms of pituitary gland volumes. We should also clearly state that our study is a pioneering study and that studies with large samples are needed to support our findings. The limitations of our study can be attributed to the small sample size, the utilization of a cross-sectional design, and the inclusion of patients using psychotropic drugs.
Keywords: adjustment disorder; volumes; pituitary; gland